![image](https://tex.z-dn.net/?f=ODZ%3A+%5Cleft+%5C%7B+%7B%7Bx-1%3E0%7D+%5Catop+%7Bx%2B2%3E0%7D%7D+%5Cright.+%3D%3E+%5Cleft+%5C%7B+%7B%7Bx%3E1%7D+%5Catop+%7Bx%3E-2%7D%7D+%5Cright.+%3D%3Ex%3E1+%5C%5C++%5Csqrt%7B+%5Csqrt%7Bx-1%7D+%2B+%5Csqrt%7Bx%2B2%7D+%7D%5E2%3D3%5E2+%5C%5C+%5Csqrt%7Bx-1%7D+%2B+%5Csqrt%7Bx%2B2%7D+%3D9+%5C%5C+%5Csqrt%7Bx-1%7D%5E2%3D%289-%5Csqrt%7Bx%2B2%7D%29%5E2+%5C%5C+x-1%3D81-18%5Csqrt%7Bx%2B2%7D%2Bx%2B2+%5C%5C+18%5Csqrt%7Bx%2B2%7D%3D84+%5C%5C+%289%5Csqrt%7Bx%2B2%7D%29%5E2%3D42%5E2+%5C%5C+81%28x%2B2%29%3D1764+%5C%5C+x%3D+%5Cfrac%7B1764-2%2A81%7D%7B81%7D++%5C%5C+x%3D+%5Cfrac%7B1602%7D%7B81%7D%3D+19+%5Cfrac%7B63%7D%7B81%7D%3D19+%5Cfrac%7B31%7D%7B27%7D++)
0} \atop {x+2>0}} \right. => \left \{ {{x>1} \atop {x>-2}} \right. =>x>1 \\ \sqrt{ \sqrt{x-1} + \sqrt{x+2} }^2=3^2 \\ \sqrt{x-1} + \sqrt{x+2} =9 \\ \sqrt{x-1}^2=(9-\sqrt{x+2})^2 \\ x-1=81-18\sqrt{x+2}+x+2 \\ 18\sqrt{x+2}=84 \\ (9\sqrt{x+2})^2=42^2 \\ 81(x+2)=1764 \\ x= \frac{1764-2*81}{81} \\ x= \frac{1602}{81}= 19 \frac{63}{81}=19 \frac{31}{27} " alt="ODZ: \left \{ {{x-1>0} \atop {x+2>0}} \right. => \left \{ {{x>1} \atop {x>-2}} \right. =>x>1 \\ \sqrt{ \sqrt{x-1} + \sqrt{x+2} }^2=3^2 \\ \sqrt{x-1} + \sqrt{x+2} =9 \\ \sqrt{x-1}^2=(9-\sqrt{x+2})^2 \\ x-1=81-18\sqrt{x+2}+x+2 \\ 18\sqrt{x+2}=84 \\ (9\sqrt{x+2})^2=42^2 \\ 81(x+2)=1764 \\ x= \frac{1764-2*81}{81} \\ x= \frac{1602}{81}= 19 \frac{63}{81}=19 \frac{31}{27} " align="absmiddle" class="latex-formula">